PENGARUH PENERAPAN MODIFIKASI PERMAINAN SEPAK TAKRAW TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS V SDN JUMPUT REJO BUDURAN SIDOARJO) - UMAM, FICKRUL (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Motivation to learn is a process for reviving a motifs into action or behavior to satisfy or meet the needs or to achive a goal (Nursalim,dkk 2007:120). In a process of learning much-needed a high motivation to students because the motivation to learn is very determining towards student learning outcomes. In connection with the activities of learning motivation of all is how to create the conditions or a process that direct students to undertake learning activities and how teachers also conduct efforts to be able to grow and provide motivation to students doing a good learning activities, so also in the sepak takraw sport learning. Modification is one effort that can be done by teachers so that the learning process of learning activity can reflect. The learning motivation of students is low then the learning objectives are obtained not maximum. The purpose of this research is: to find out whether the implementation of improvement measures and modifications to the sepak takraw game to the learning motivation of students in teaching of physical education, sport and health. The kind of research that will be used in this type of research is descriptive-quantitative approach. In this study to measure the learning motivation of students in teaching of physical education, sport and health, then use the motivation now consist of 27 items quastion. The sample of this research is the grade V Jumput rejo country elementary school, Sukodono, Sidoarjo that amounted to 39 students. Calculation analysis of known data description: there is the influence of the application of a modified sepak takraw game  to the learning motivation of students in the teaching of physical education, sport and health on the grade V Jumput rejo country elementary school, Sukodono, Sidoarjo whit an increase of 2.55%. this is indicated in the calculation of uji-t that value of thitung (2,86) is large than the ttabel (2,021). Keywords: Modification, Spak Takraw, Learning Motivation Of Students.